Heat conduction problem for a composite cylinder with imperfect contact conditions between its layers - Мішуріс, Генадій; Процеров, Юрій; Вайсфельд, Наталя; Журавльова, Зінаїда (Київський національний університет імені Тараса Шевченка, 2026)
The paper considers the thermal conductivity problem for a multilayer cylinder, taking into account the influence of interface contrasts, which significantly change the mechanisms of heat transfer and complicate the determination of effective thermal conductivity. The aim of the study is to obtain non-ideal contact conditions between layers for different orders of thermal conductivity coefficients in the presence of an interlayer. Based on an asymptotic approach, three types of coupling conditions are derived that correspond to the characteristic modes of interaction between the layers. The proposed method provides the possibility of  correctly describing key thermal and mechanical effects using simplified relationships suitable for further engineering applications. Pages of the article in the issue: 143 - 146 Language of the article: Ukrainian

Розглянуто задачу теплопровідності для багатошарового циліндра з урахуванням впливу міжфазних контрастів, що істотно змінюють механізми теплоперенесення й ускладнюють визначення ефективної теплопровідності. Метою дослідження є отримання неідеальних умов контакту між шарами для різних порядків коефіцієнтів теплопровідності за наявності прошарку. На основі асимптотичного підходу виведено три типи умов спряження, що відповідають характерним режимам взаємодії шарів. Запропонований метод забезпечує можливість коректного опису ключових теплових і механічних ефектів за допомогою спрощених співвідношень, придатних для подальших інженерних застосувань.
Задача теплопровідності для складеного циліндру з неідеальними умовами контакту між його шарами
Keywords: composite cylinder; heat conduction; imperfect contact conditions; складений циліндр; теплопровідність; неідеальні умови спряження